Mitigating the carbon footprint and improving productivity of ruminant livestock agriculture using a red seaweed. (20th June 2020) - Kinley, Robert D.; Martinez-Fernandez, Gonzalo; Matthews, Melissa K.; de Nys, Rocky; Magnusson, Marie; Tomkins, Nigel W.
Abstract: Ruminants are responsible for a large proportion of agricultural greenhouse gas emissions in the form of methane. This can be managed. It is a global initiative to increase productivity of the livestock sector to meet a growing population, but with emphasis on decreasing enteric methane to achieve emissions targets. We investigated the marine red macroalga (seaweed) Asparagopsis taxiformis as a feed ingredient to fundamentally eliminate enteric methane in beef cattle fed a high grain diet and provide evidence of improved livestock production performance. Asparagopsis was included in the feed of Brahman-Angus cross steers at 0.00%, 0.05%, 0.10%, and 0.20% of feed organic matter. Emissions were monitored in respiration chambers fortnightly over 90 d of treatment, steers were weighed weekly prior to feeding, feed intake monitored daily, rumen fluid samples collected in conjunction with respiration chambers for assessment of rumen function, feces were collected for bromoform residue analysis, and meat, organ, and fat were collected post slaughter for residue analysis and sensory evaluation. Steers receiving 0.10% and 0.20% Asparagopsis demonstrated decreased methane up to 40% and 98%, and demonstrated weight gain improvements of 53% and 42%, respectively. There was no negative effect on daily feed intake, feed conversion efficiencies, or rumen function, and no residues or changes in meat eating quality were detected. Commercial production of Asparagopsis could create new economies, and with low inclusion rates of this seaweed in ruminant diets the industry has the potential to revolutionize management of greenhouse gas emissions across the ruminant livestock sector with complementary benefits to the environment, and economy of the wider agriculture sector. Highlights: The red seaweed Asparagopsis induces unprecedented enteric methane mitigation. Productivity of beef cattle can be improved by a seaweed feed ingredient. Asparagopsis provides an option to achieving carbon neutral red meat production. No negative impacts induced by substantial methane abatement in beef cattle.